Hybrid thermoelectric generators-renewable energy systems: A short review on recent developments - Zahra Wehbi; Rani Taher; Jalal Faraj; Cathy Castelain; Mahmoud Khaled (Energy Reports, 2022)
The development of different renewable energy techniques has shown their ability in limiting the environmental crisis and meeting future needs. In recent years many efforts have been made in order to produce hybrid systems that work on integrating renewable energy systems with thermoelectric generators (TEGs) in order to increase energy efficiency. This review attempts to discuss and summarize different configurations of hybridizing TEGs with different renewable energy sources (solar, fuel cell, biomass) underlying the concepts and approaches used to reach these hybridizations. This review will give necessary information about this type of hybridization and encourage for future research due to its promising results.